Edukasi Bahaya Rokok dan Kaitannya dengan Stunting Menggunakan Media Edukatif Ular Tangga pada Siswa SMPN 7 Tamalatea Desa Bontosunggu - St Rosmanely; Nur Alisa Rahim; Inayah Nur Rahmaniyah; Fitri Siska Busdir; Suci Rahmadani (Yayasan Literasi Sains Indonesia, 2025)
Cigarette smoking is one of the major risk factors that adversely affects health, not only for active smokers but also passive smokers. In addition, exposure to cigarette smoke contributes to the incidence of stunting in children through various mechanisms, such as impaired nutrient absorption and increased risk of infection. Therefore, effective educational efforts are needed to increase adolescents' understanding of the dangers of smoking and its impact on child growth and the link to stunting. This study aims to increase the knowledge of SMPN 7 Tamalatea students about the dangers of smoking and its relationship with stunting and evaluate the effectiveness of education using educational media in the form of snakes and ladders games for students of SMPN 7 Tamalatea, Bontosunggu Village, Tamalatea District, Jeneponto Regency. Educational activities were carried out using an interactive lecture method using a slide presentation and a snakes and ladders game specifically designed with material about the dangers of smoking and its impact on health. Evaluation was carried out by comparing the results of the pre-test and post-test using the Paired T-Test test to see the increase in students' understanding before and after the intervention related to smoking hazard education. The results of statistical analysis showed an increase in the average score of students' knowledge from 3.66 ± 1.84 before education to 6.56 ± 1.81 after education, with a p value = 0.000 (p < 0.05), which indicates a significant increase in knowledge after the intervention.